Adaptive Dynamic Tariff Factor for Distribution Network Congestion Mitigation - Boontagool, Pawarit; Wirasanti, Paramet (International Conference on Electrical and Electronics Engineering, 2024)
Network congestion is the main problem in the distribution system. It is necessary to study dynamic tariff methods to curtail network congestion problems. Through the use of dynamic tariffs, regulatory prices have the potential to be either positive (tariff) or negative (subsidy). To address these challenges, stakeholders have implemented different types of tariffs, making iterative adjustments in pricing and/or engaging in contractual arrangements driven by incentives. However, dynamic tariffs cannot handle a large number of distribution energy resources. Here we show this research to determine the dynamic tariff using two calculation methods (line constraint and baseline load). The adaptive dynamic tariff factor has been used to adjust the price of electricity via real data recorded from a five-feeder distribution network. The results demonstrated that the line constraint method can reduce electricity prices up to 28.16% and increase electricity prices by 37.25%, providing an incentive for consumers to change their schedule and reduce the congestion problem.